Pengaruh Kompetensi Pedagogik dan Kedisiplinan Guru Terhadap Kinerja Guru - Emerda, Lia (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the influence of pedagogical competence and teacher discipline on teacher performance at SD Negeri 04 Jaya Pura. Pedagogical competence includes teachers’ ability to design, implement, and evaluate the learning process, while teacher discipline involves teachers’ commitment and consistency in carrying out their duties. The research method used is a quantitative approach with a case study design. Data were obtained through questionnaires distributed to all teachers at SD Negeri 04 Jaya Pura and analyzed using linear regression techniques to measure the influence of two independent variables on teacher performance. The results of the study indicate that both pedagogical competence and teacher discipline have a significant influence on teacher performance. Teachers with high pedagogical competence are better able to manage the learning process effectively, while teacher discipline directly affects the consistency and quality of their performance in the school environment. This study concludes that improving pedagogical competence and teacher discipline is very important to improve their performance, which in turn will have a positive impact on the quality of education.